(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
This paper analyses the stability of the mining blocks by the Monte Carlo method in Estonian oil shale mines, where the room-and-pillar mining system is used. The pillars are arranged in a singular grid. The oil shale bed is embedded at the depth of 40-75 m. The processes in overburden rocks and pillars have caused the subsidence of the ground surface. Visual Basic for Application was used for the modeling. Through Monte Carlo simulation, room-and-pillar stable parameters can be calculated. Model allows determination of the probability of spontaneous collapse of the pillars and surface subsidence by the parameters of registered collapsed mining blocks. Proposed method suits as an express-method for stability analysis and failure prognosis. It is applicable in different geological conditions, where the room-and-pillar mining system is used.